PENGARUH MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PAKET INTERNET TELKOMSEL DI FAKULTAS EKONOMI UNTAN - admin, Nanang Fauji B11112042 (Jurnal Manajemen Update, 2016)
The purpose of this study was to determine the influence of Brand, Price and Quality Products Buying Decision Against Telkomsel internet packages at the students of the Faculty of Economics, University Tanjungpura. Data were collected by questionnaire. The sampling technique used was purposive sampling technique with a sample size of 100 respondents. Its population is a student at the Faculty of Economics, University Tanjungpura Pontianak. The analysis technique used using SPSS version 23. Based on the feasibility test models obtained significance value <0.05, making it feasible to use the model. The results of this study show that 1) Brand and Quality of Products proven to significantly influence the purchase decision. 2) The price does not significantly influence the purchase decision. Keyword : Brand, price, product quality, and purchase decisions